MYH knockdown in pancreatic cancer cells creates an exploitable DNA repair vulnerability - Ephraums, James; Youkhana, Janet; Raina, Aparna S.; Schulstad, Grace; Croft, Kento; Mawson, Amanda; Kokkinos, John; Gonzales-Aloy, Estrella; Ignacio, Rosa Mistica C.; McCarroll, Joshua A.; Boyer, Cyrille; Goldstein, David; et al. (Neoplasia (New York, N.Y.), 2025)
Pancreatic ductal adenocarcinoma (PDAC) has a poor 5-year survival rate of just 13 %. Conventional therapies fail due to acquired chemoresistance. We previously identified MutY-Homolog (MYH), a protein that repairs oxidative DNA damage, as a therapeutic target that induces apoptosis in PDAC cells. However, we did not understand the mechanism driving these anti-PDAC effects, nor did we have a means to therapeutically inhibit MYH. In this study, we demonstrated that MYH inhibition induces DNA damage and checkpoint activation in PDAC cells. Using a clinically-relevant PDAC mouse model, we showed that therapeutic MYH-siRNA delivery using Star 3 nanoparticles increased intratumoural PDAC cell death, but did not inhibit tumour growth. Finally, we showed that MYH knockdown in PDAC cells sensitised them to the anti-proliferative and anti-clonogenic effects of oxaliplatin and olaparib. Our findings identify a potential novel therapeutic approach for PDAC that induces a therapeutically exploitable DNA repair vulnerability.